Vitamin D receptor expression in human bone tissue and dose-dependent activation in resorbing osteoclasts - Zarei, Allahdad; Morovat, Alireza; Javaid, Kassim; Brown, Cameron P (Bone research, 2016)
The effects of vitamin D on osteoblast mineralization are well documented. Reports of the effects of vitamin D on osteoclasts, however, are conflicting, showing both inhibition and stimulation. Finding that resorbing osteoclasts in human bone express vitamin D receptor (VDR), we examined their response to different concentrations of 25-hydroxy vitamin D [25(OH)D ] (100 or 500 nmol L ) and 1,25-dihydroxy vitamin D [1,25(OH) D ] (0.1 or 0.5 nmol L ) metabolites in cell cultures. Specifically, CD14+ monocytes were cultured in charcoal-stripped serum in the presence of receptor activator of nuclear factor kappa-B ligand (RANKL) and macrophage colony-stimulating factor (M-CSF). Tartrate-resistant acid phosphatase (TRAP) histochemical staining assays and dentine resorption analysis were used to identify the size and number of osteoclast cells, number of nuclei per cell and resorption activity. The expression of VDR was detected in human bone tissue ( ) by immunohistochemistry and cell cultures by western blotting. Quantitative reverse transcription-PCR (qRT-PCR) was used to determine the level of expression of vitamin D-related genes in response to vitamin D metabolites. VDR-related genes during osteoclastogenesis, shown by qRT-PCR, was stimulated in response to 500 nmol L of 25(OH)D and 0.1-0.5 nmol L of 1,25(OH) D , upregulating cytochrome P450 family 27 subfamily B member 1 ( ) and cytochrome P450 family 24 subfamily A member 1 ( ). Osteoclast fusion transcripts transmembrane 7 subfamily member 4 ( ) and nuclear factor of activated T-cell cytoplasmic 1 ( ) where downregulated in response to vitamin D metabolites. Osteoclast number and resorption activity were also increased. Both 25(OH)D and 1,25(OH) D reduced osteoclast size and number when co-treated with RANKL and M-CSF. The evidence for VDR expression in resorbing osteoclasts and low-dose effects of 1,25(OH) D on osteoclasts may therefore provide insight into the effects of clinical vitamin D treatments, further providing a counterpoint to the high-dose effects reported from experiments.